How does organizational performance in the education sector improve? Learning and Growth-perspective - Siti Aisyah; Adisthy Shabrina Nurqamarani; A.M. Wibowo; Cherly Kemala Ulfa (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2023)
The purpose of this study is to measure whether organizational performance in the education sector could be improved through a learning and growth perspective, which involves constructs of human capital, information capital, and organizational capital. This research uses a quantitative approach with the survey as a data collection method and the structural equation model as the analysis method via Smart PLS software to measure the relationship between human, information, and organizational capital with organizational performance, from the perspective of learning and growth. This study concluded that human capital (HC) and Informational Capital (IC) simultaneously have a strong relationship to organizational performance (OP) with Organizational Capital (OC) as a mediating variable. Directly, HC and OC have a significant relationship with OP. While IC has a weak relationship with OP. These results conclude that without HC and OC, IC is a variable that functions to encourage and utilize HR work to form OC and OP. These findings strengthen the theory about the importance of human resource management in the education sector through aspects of meeting the needs of knowledge development, and skill competencies that keep up with developments. This finding also strengthens the theory that claim that learning and growth factors influence organizational performance along the internal process, financial, and customer per- spectives.